Highly Selective Uricase-Based Quantification of Uric Acid Using Hydrogen Peroxide Sensitive Poly-(vinylpyrrolidone) Templated Copper Nanoclusters as a Fluorescence Probe - Ramar Rajamanikandan; Malaichamy Ilanchelian; Heongkyu Ju (Chemosensors, 2023)
We reported on uric acid (UA) detection using a new fluorescence-based assay: poly-(vinylpyrrolidone) templated copper nanoclusters (PVP-CuNCs) with uricase in an aqueous medium, such as human urine with uricase. These nanoclusters were synthesized in a simple wet chemical method and their morphological and optical properties were examined with the aid of high-resolution transmission electron microscopy and optical absorbance/emission spectroscopy. The PVP-CuNCs acted as the fluorescence indicators that used the enzyme-catalyzed oxidation of UA with uricase. Adding UA into the hybrid PVP-CuNCs/uricase solution caused enzyme-catalyzed oxidation to occur, producing hydrogen peroxide (H2O2), allantoin, and carbon dioxide. The fluorescence intensity of PVP-CuNCs is decreased by this biocatalytically generated H2O2, and this decrease is proportional to the UA level. A calibration plot showed the linear relationship with the negative slope between fluorescence intensity and UA in the range of 5–100 × 10−7 mol/L. The limit of detection (LOD) of UA was estimated as 113 × 10−9 mol/L. This fluorescent probe turned out to be highly specific for UA over other biologically relevant molecules. The demonstrated capability of the PVP-CuNCs as the nanoprobes for quantification of the UA levels in human urine samples could potentially pave the way toward medical applications where a super-sensitive, cost-effective, and UA-specific diagnosis was required.